On the run: fugitive life in an American city - Goffman, Alice (Fieldwork encounters and discoveries, 2014)
The 6th Street boys and their legal entanglements -- The art of running -- When the police knock your door in -- Turning legal troubles into personal resources -- The social life of criminalized young people -- The market in protections and privileges -- Clean people -- Conclusion: a fugitive community -- Epilogue: leaving 6th Street -- Appendix. A methodological note